(untitled) (Revista da Faculdade de Odontologia - UPF, 2017)
The collagenous matrix plays a fundamental role in the process of bone regeneration, so it is essential to study how it is primarily formed in situations in which critical bone defects are created. Objective: this study seeks to quantify the collagenous matrix formed in critical bone defects in the calvaria of mice over the process of bone regeneration promoted by the association of poly(lactide-co-glycolide) (PLGA) porous scaffolds and stem cells from deciduous teeth (SCDT). In addition, this study attempted to establish a precise protocol for the digital quantification of collagen through a histological method. Materials and method: Nine Wistar rats were used, in which critical defects of 8.0 mm of diameter were made in their calvarium. The animals were divided into three groups (n = 9): I – PLGA scaffolds; II – PLGA scaffolds/SCDT; III – PLGA scaffolds/SCDT maintained in osteogenic medium for 13 days. Within sixty postoperative days, calvaria were removed for histometric analysis following a digital protocol. A specific digital analysis method was designed for this study, in which a more precise quantification and differentiation between collagen fibers and non-collagenous tissue was possible, excluding factors that would normally alter the results. Results: it was noted that the association of PLGA scaffolds and SCDT maintained in osteogenic medium resulted in collagen matrix formation statistically higher than the other groups (p